REVITALIZATION OF MOSQUE FUNCTIONS IN EMPOWERING CITY ISLAMIC COMMUNITIES BANDAR LAMPUNG - Kurniawan, Agus Tri; Bahri, Bahri; Mukmin, Hasan; Yanti, Fitri (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
The mosque reflects all the activities of Muslims, the mosque is a benchmark and indicator of the welfare of the people both physically and spiritually. There are several mosques in Indonesia that are not carrying out their functions properly, due to the increasing pandemic and the lack of mosque administrators who have contributed to providing potential and ideas in empowering mosques so that the functions of mosques have decreased. Mosque revitalization has indicators of Idaroh Maddy or (Physical Management), Idaroh Ruhiy or (Funcsional Management). The mosque even has areas as pilot centers, namely the Idaroh (Managerial), Imaroh (Development and Empowerment) and Ri'ayah (Maintenance) sections. The function of the mosque at this time must at least fulfill a number of things, namely: the mosque as a center for ritual worship, an Islamic education center, a center for economic empowerment for the people, a health service center for the people, a center for social services for the people, and the mosque as a center for information and communication for the people. This research method is descriptive qualitative which collects primary and secondary data by means of interviews, observation and documentation. Based on the results of data analysis, the revitalization of the functions of the Al Furqon mosque in Bandar Lampung, the Ad Du'a Way Halim Mosque in Bandar Lampung and the Jami Al Anwar Masjid Teluk Betung Selatan are active in several functions, namely 1) Primary Function. 2) Worship Function. 3) Secondary Functions. 4) Educational Function. 5) Economic Function. 6) Community Empowerment Function. 7) Support Functions. Of the three mosques in the city of Bandar Lampung which represent other mosques in advancing and prospering mosques and revitalizing the functions of mosques, namely the functions of mosques have changed and shifted from time to time. The mosque currently functions as a forum for da'wah, economic, social, educational, congregational development, congregational welfare, training. Based on the implementation of the mosque's function in community empowerment, a participatory approach and congregation-based collaborative collaboration is found as a form of community empowerment innovation. The author's suggestions and recommendations are for all mosque administrators to activate the functions of mosque organizations that are less productive by evaluating them so that they will be better in the future